Phonological and semantic verbal fluency: a comparative study in hearing-impaired and normal-hearing people - Isadora Machado Monteiro dos Santos; Júlia Santos Costa Chiossi; Alexandra Dezani Soares; Letícia Neves de Oliveira; Brasília Maria Chiari (CoDAS)
PURPOSE: To compare the performance of hearing-impaired and normal-hearing people on phonologic and semantic verbal fluency tests. METHODS: A cross-sectional study was conducted with 48 hearing-impaired adults and 42 individuals (control group) with no hearing or language complaints. Sociodemographic data were collected, as well as the characteristics of hearing loss and of the electronic auditory device (hearing aids or cochlear implant), when relevant. Verbal fluency was tested in two different tasks: by semantic category (animals) and by phonology (letter F). RESULTS: Educational level has influenced the results of fluency tests in both groups, with more evidence in the hearing-impaired subjects (p<0.001). Hearing-impaired subjects showed worse performance in verbal fluency tests when compared to normal-hearing people in groups with up to 10 years of schooling. In the comparison of performance in the two tests, both groups showed better results in the semantic fluency task. CONCLUSION: The hearing-impaired subjects with low educational level evoked fewer words in semantic and phonologic verbal fluency tests in comparison to normal-hearing subjects. Educational level is a relevant issue to the study of verbal fluency in deaf and hearing-impaired people.